2021
DOI: 10.1136/jclinpath-2021-207631
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-specific accumulation oftelomerase reverse transcriptase(TERT) mRNA inTERTpromoter mutated follicular thyroid tumours visualised by in situ hybridisation: a possible clinical screening tool?

Abstract: AimsUpregulation of the telomerase reverse transcriptase (TERT) gene is a frequent finding in follicular thyroid carcinomas (FTCs) with metastatic features. The augmented expression is usually caused by TERT promoter mutations. As TERT protein immunohistochemistry might not correlate to TERT mRNA levels in follicular thyroid tumours, we therefore sought to determine if visualisation of TERT mRNA through in situ hybridisation could highlight high-risk cases.MethodsWe collected formalin-fixated paraffin-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…TERT aberrancies may exhibit spatial heterogeneity in follicular thyroid tumors, which has been shown for TERT promoter mutations [17,18] as well as for TERT mRNA expression visualized by ISH [10]. It was therefore expected that some heterogeneity could be observed regarding the expression of 5hmC; it is however interesting that as many as half of all cases showed heterogeneous expression patterns -a nding that lacks a credible explanation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TERT aberrancies may exhibit spatial heterogeneity in follicular thyroid tumors, which has been shown for TERT promoter mutations [17,18] as well as for TERT mRNA expression visualized by ISH [10]. It was therefore expected that some heterogeneity could be observed regarding the expression of 5hmC; it is however interesting that as many as half of all cases showed heterogeneous expression patterns -a nding that lacks a credible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…TERT promoter mutations and TERT gene expression are not unequivocally needed for the global loss of 5hmC in thyroid cancer. There is much to be revealed regarding the biology of TERT promoter mutations in follicular thyroid tumors, as TERT protein expression itself may not be correlated to TERT promoter mutations and TERT mRNA expression [9] as well as the recent observation of nuclear-speci c TERT mRNA expression [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, whereas TERT immunohistochemistry (IHC) is not yet considered a reliable method, studies using TERT mRNA in situ hybridization (ISH) have shown promising results. 9,10 5-Hydroxymethylcytosine (5hmC) immunoreactivity is decreased in various malignant tumors, such as melanoma 11 and glioma 12 as well as in papillary thyroid carcinoma (PTC). 13,14 5hmC is produced when 5-methylcytosine is demethylated via ten-eleven translocation (TET) enzymes, and 5hmC may thus serve as an epigenetic marker of global de-methylation events across the genome.…”
Section: Introductionmentioning
confidence: 99%